(untitled) (American Journal of Technology and Applied Sciences, 2025)
With an uncomplicated pregnancy in a woman’s body, a number of adaptive and adaptive processes develop (hypervolemia, fluid accumulation, changes in the content of electrolytes and non-electrolytes), in which the kidneys are directly involved. On the other hand, the appearance of uteroplacental blood circulation, an increase in regional hemodynamics during pregnancy cannot but affect the functional state of the kidneys of a pregnant woman. During physiological pregnancy, specific changes in kidney function occur, aimed at ensuring the normal process of gestation. However, ultrasound studies of the kidneys using intravital biopsy did not reveal any significant changes in the structure of the parenchyma.